2011
DOI: 10.1007/s12185-011-0906-8
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of malignant cells by effusion drainage alone in two patients with HHV-8-unrelated HIV-negative primary effusion lymphoma-like lymphoma

Abstract: Primary effusion lymphoma (PEL) is a rare type of non-Hodgkin lymphoma usually confined to the body cavities of predominantly immunosuppressed patients infected with human herpes virus-8 (HHV-8). In PEL, malignant cells are usually negative for B-cell markers, such as CD19, CD20, and CD79a, but are positive for activation and plasma cell-related markers, such as CD30, CD38, and CD138. It has been reported that HHV-8-unrelated PEL shows high expression of B-cell markers, which is referred to as PEL-like lymphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…The mean survival time of PEL is approximately 4-6 months; however, in the review of Adiguzel et al [4] of 31 cases of HHV-8-negative effusion lymphoma, the mean survival time was 10.1 months and the mean follow-up period of 13 living patients was 19.5 months [4]. In our two cases, the tumor regressed without any treatment other than drainage of the effusion, and 7 cases of HHV-8-negative effusion lymphoma presenting a similar phenomenon have been reported in the literature [4,5,6,7,8,10]. In 5 cases (including our 2 cases) of these 9 cases, lymphoma cells were involved in the pericardial effusion.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The mean survival time of PEL is approximately 4-6 months; however, in the review of Adiguzel et al [4] of 31 cases of HHV-8-negative effusion lymphoma, the mean survival time was 10.1 months and the mean follow-up period of 13 living patients was 19.5 months [4]. In our two cases, the tumor regressed without any treatment other than drainage of the effusion, and 7 cases of HHV-8-negative effusion lymphoma presenting a similar phenomenon have been reported in the literature [4,5,6,7,8,10]. In 5 cases (including our 2 cases) of these 9 cases, lymphoma cells were involved in the pericardial effusion.…”
Section: Discussionsupporting
confidence: 74%
“…Such cases have been largely reported from Japan and have been designated ‘HHV-8-negative PEL' or ‘PEL-like lymphoma' [2,3,4,5,6,7,8]. However, the clinical and biological characteristics of these tumors differ from those of PEL.…”
Section: Introductionmentioning
confidence: 99%
“…Although the neoplastic cells of PEL-like lymphoma show immunoreactivity for pan-B-cell markers such as CD19, CD20, and CD79a, the neoplastic cells of PEL lack such immunoreactivity. With regard to prognosis, while PEL is extremely aggressive, PEL-like lymphoma has a more indolent course and some patients including our case recover with drainage alone [10,15].…”
Section: Discussionmentioning
confidence: 76%
“…PEL has a strong prognosis for mortality during the early phase, whereas the literature includes numerous reports of favorable responses to chemotherapy in patients with PEL‐LL 7. It has been reported that etoposide, prednisolone, vincristine, cyclophosphamide, doxorubicin (DA‐EPOCH therapy or CDE therapy), or ganciclovir is effective for PEL,8, 9 but treatment‐based evidence for PEL and PEL‐LL has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Terasaki et al 7. have reported disappearance of malignant cells by first drainage with PEL‐LL, and it seems that performing secondary drainage becomes difficult.…”
Section: Discussionmentioning
confidence: 99%